Orientalisme dan Hadits : Kritik terhadap Sanad Menurut Pemikiran Joseph Schacht - Irzak Yuliardy Nugroho (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2020)
The Origins of Muhammadan Jurisprudence is the work of Joseph Schacht which is the foundation of Islamic scholarship in the West. This is the main book about the field of study which later was known as